Sophists and skeptics: from the semantic of names to historical vilification - Rennyer, Wesley (Sofia, 2025)
More than any school of thought, the early Sophists were the ones who most clearly and tangibly anticipated, in their epistemological positions, a form of thinking akin to the Pyrrhonian skeptical tradition. However, beyond the conformity of thought between the Sophists and the Skeptics, these two 'schools' shared the same type of hostile reception from the philosophical tradition – a reception that led to the historical disqualification which placed the skeptical-sophistic thought in a lesser position in the history of ideas. As a result, the terms themselves became corrupted, no longer meaning what they originally meant, and acquired pejorative connotations. In light of this, the aim of this work is to analyze the primary meaning and the historical nuances of the terms σοφιστής and σκεπτικός, as well as to investigate the long process of philosophical disqualification that these two traditions underwent, so that the original meaning of the terms and the historical repudiation of these two traditions can be clarified.
Keywords: sophistry; skepticism; historical vilification